👤

Bonjour, j'aurai besoin d'aide pour ces exercices de math.
Développer, réduire l’expression suivante : A = (3x - 2)² + (x - 3)(x + 3).

Factoriser : B = (2x + 3)² - (2x + 3)(x - 2)

C = 4x² - 9

Merci beaucoup.


Répondre :

1) A = (3x - 2)² + (x - 3) (x + 3)
A = (3x)² - 2 * 3x * 2 + 2² + x² - 3²
A = 9x² - 12x + 4 + x² - 9
A = 10x² - 12x - 5

2) B = (2x + 3)² - (2x + 3) (x - 2)
B = (2x + 3) [(2x + 3) - (x - 2)]
B = (2x + 3) (2x + 3 - x + 2)
B = (2x + 3) (x + 5)

C = 4x² - 9
C = (2x)² - 3²
C = (2x - 3) (2x + 3)